The impact of supplementing vitamin D through different methods on the prognosis of COVID-19 patients: a systematic review and meta-analysis - Zhang, Xiangqun; Wu, Junyuan; Dong, Hongmeng; Shang, Na; Li, Yixuan; Zhang, Ying; Guo, Shubin; Mei, Xue (Frontiers in Nutrition, 2024)
Objective To analyze the impact of different methods of Vitamin D administration on the prognosis of COVID-19 patients. Methods A comprehensive literature search was conducted across four databases: PubMed, Embase, Web of Science, and Cochrane, up to January 5, 2024. Eligible studies included randomized controlled trials and cohort studies that compared Vitamin D supplementation with control groups in COVID-19 patients. Outcomes of interest were mortality rate, ICU (Intensive Care Unit) admission rate, length of hospital stay, and endotracheal intubation rate. Subgroup analyses were performed based on the dosing regimen (single-dose vs. continuous-dose), total Vitamin D intake within 14 days (≥100,000 IU vs. <100,000 IU), and baseline serum Vitamin D levels (deficient group: 25OHD < 30 ng/mL vs. non-restricted group). A random-effects model was employed for meta-analysis to account for heterogeneity among studies. Results A total of 21 studies involving 4,553 participants were included. In terms of mortality, Vitamin D supplementation significantly reduced the mortality rate (RR = 0.72, 95% CI: 0.54–0.94, I2 = 54%, p = 0.02), with continuous dosing being more effective (RR = 0.53, 95% CI: 0.34–0.83, I2 = 55%, p = 0.006) compared to single-dose (RR = 0.88, 95% CI: 0.69–1.12, I2 = 21%, p = 0.3), and lower total doses (<100,000 IU) showing greater benefit (RR = 0.30, 95% CI: 0.21–0.44, I2 = 0%, p < 0.0001). Mortality was significantly reduced in the Vitamin D-deficient group (25OHD < 30 ng/mL) (RR = 0.73, 95% CI: 0.59–0.89, I2 = 0%, p = 0.002) but not in the non-restricted group. Regarding ICU admission, supplementation reduced ICU admission rates (RR = 0.58, 95% CI: 0.38–0.88, I2 = 74%, p = 0.01), with continuous dosing (RR = 0.44, 95% CI: 0.22–0.90, I2 = 74%, p = 0.02) being more effective than single-dose (RR = 0.79, 95% CI: 0.61–1.03, I2 = 22%, p = 0.08), and lower doses (<100,000 IU) providing more significant reduction (RR = 0.31, 95% CI: 0.21–0.47, I2 = 0%, p = 0.001). ICU admission rates were significantly reduced in the Vitamin D-deficient group (RR = 0.63, 95% CI: 0.42–0.93, I2 = 0%, p = 0.02) but not in the non-restricted group (RR = 0.59, 95% CI: 0.32–1.11, I2 = 86%, p = 0.1). For length of hospital stay, no significant differences were observed between Vitamin D and control groups (MD = −1, 95% CI: −2.16 to 0.16, p = 0.13), and subgroup analyses by dosing regimen, total dose, and baseline Vitamin D levels also showed no significant differences. Similarly, for endotracheal intubation, there was no significant difference in intubation rates between groups (RR = 0.78, 95% CI: 0.56–1.08, p = 0.13), and subgroup analyses confirmed no significant effect of different dosing strategies or baseline Vitamin D status on intubation rates. Conclusion Vitamin D supplementation improves clinical outcomes in COVID-19 patients by reducing mortality and ICU admission rates, particularly when administered continuously with a total dose of less than 100,000 IU over 14 days, and among those with baseline Vitamin D deficiency (25OHD < 30 ng/mL). However, there were no significant effects on the length of hospital stay or endotracheal intubation rates, regardless of the dosing regimen or baseline Vitamin D levels. These findings emphasize the importance of considering both the total dose over 14 days and baseline Vitamin D status to optimize therapeutic benefits.